Validação de bioensaio por cultura de células para avaliação de potência de rhEPO e correlação com bioensaio in vivo e métodos cromatográficos - Machado, Francine Trevisan (2014)
Erythropoietin is a hematopoietic hormone and the main physiological function is the induction of erythropoiesis. Recombinant DNA technology enabled cloning and expression of rhEPO gene to produce recombinant human erythropoietin (rhEPO). It is a sialoglycoprotein composed of 165 amino acids chain and about 40% of the molecule consists of carbohydrates, important for biological activity due to the presence of sialic acid residues at the termini of chains affecting its half-life. In the present study an alternative in vitro cell culture-based assay using TF-1 cell line was validated, to be used in conjunction with a reversed-phase liquid chromatography method with fluorescence detection (F-RP-LC) validated to determine the content of sialic acids. The values obtained for the sialic acids were higher than 126.83 ng/μg, and the biotechnology-derived products were subjected to the cell culture bioassay giving potencies 2.91% ± 0.85 lower related to the bioassay in normocythaemic mice, with significant correlation calculated by the Pearson coefficient (r = 0.9947). In parallel, it was determined the content/potency of the products by the validated reversed-phase and size-exclusion liquid chromatography methods that showed mean results 3.14% higher and 2.87% lower, respectively, compared to the in vitro bioassay. It was demonstrated that in vitro cell culture bioassay represent a valid alternative to the in vivo bioassay for the potency assessment of rhEPO, in the context of the reduction and/or replacement of animals. Likewise, correlation of the results obtained with the physicochemical methods, represents advances for the characterization of the biomolecule, which can be applied to the production steps and for the quality control, contributing to assure the batch-to-batch consistency of the bulk and the finished biological products of rhEPO.